Vegetable distributor business development strategy (Case study at PT XYZ) - Mangkudilaga, Erwin Taufik Krisnadi; Jahroh, Siti; Rifin, Amzul (Indonesian Journal of Multidisciplinary Science, 2023)
The vegetable and fruit commodity business has good prospects for continued development. Vegetable production continues to increase from year to year. On the other hand, Indonesian people's consumption of vegetables is still low. PT XYZ is a company operating in the vegetable distributor sector. It faces the challenges of increasingly fierce competition and changes in customer purchasing patterns since the Covid-19 outbreak. The aim of this research was to identify business models, formulate alternative strategies, formulate priority strategies and formulate new business models that can be implemented to develop PT XYZ's business. Identification of PR XYZ's business model was carried out using the Business Model Canvas (BMC). Next, a SWOT analysis was carried out on the 9 elements of the Business Model Canvas, the results of which were also used to carry out IE analysis (EFE and IFE). From the IE analysis, PT XYZ's position was in quadrant V (Hold and Maintain). Commonly used strategies are Market Penetration and Product Development). From SWOT Matrix analysis (SO, WO, ST and WT). on the key factors of EFE and IFE, alternative strategies were obtained which were then prioritized using the Quantitative Strategic Planning Matrix (QSPM), namely: forming a research and development section, evaluating vegetable processing processes, developing vegetable derivative products, carrying out more active marketing activities, developing marketing to the hotel, restaurant and cafe (HOREKA) segment, mapping vegetable suppliers,  developing marketing to the online segment, creating a cooperation program that can bind suppliers, and opening a warehouse in Jakarta to reduce costs.